Cosmological and Theological Conception of Society - Čiuldė, Edvardas (Problemos, 1989)
Based upon social theories of Plato and Augustinus two conceptions of society, na mely, cosmological one and theological one are discussed in the paper. The peculiarities of the social knowledge in the two neighbouring epochs are cleared up. Finally, the histo rical grounds of the two conceptions are considered.